IRE1 is a promising therapeutic target in pancreatic cancer - Lucas, Denise; Sarkar, Tamal; Niemeyer, Clara Y.; Harnoß, Julian-Camill; Schneider, Martin; Strowitzki, Moritz; Harnoß, Jonathan M. (American journal of physiology. Cell physiology, 2025)
Pancreatic cancer (PC) is one of the most aggressive malignancies, characterized by an increasing incidence and unfavorable prognosis. Despite recent advances, surgical resection combined with chemotherapy remains the only potentially curative therapeutic option. Therefore, it is of paramount importance to identify novel therapeutic targets and develop effective treatment strategies. Pancreatic ductal adenocarcinoma (PDAC), the most prevalent form of PC, originates from exocrine cells and is subjected to both intrinsic and extrinsic cellular stresses, including oncogene activation, loss of tumor suppressors, a hypoxic and immunosuppressive tumor microenvironment (TME), and chemotherapy, causing an accumulation of misfolded proteins within the endoplasmic reticulum (ER). The loss of ER proteostasis activates the unfolded protein response (UPR), an intracellular sensing-signaling network that enables cancer cells to alleviate ER stress and restore cellular proteostasis. The key UPR sensor inositol-requiring enzyme 1 (IRE1) is an ER membrane protein that activates the transcription factor X-box protein 1 spliced through its cytoplasmic kinase-RNase module, promoting protein folding, secretion capacity, and proteasomal degradation of misfolded proteins. In addition, it regulates IRE1-dependent decay of various mRNA and functions through scaffold interactions. In this review, we synthesize current evidence on the cell-autonomous and cell-non-autonomous roles of IRE1 in tumor initiation, progression, metastasis, and drug resistance in PDAC and outline key research directions to investigate IRE1 as a potential therapeutic target.
Vorab veröffentlicht: 17. Januar 2025
Gesehen am 07.08.2025